1995
DOI: 10.1002/depr.3050030503
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis linking the noradrenergic and dopaminergic systems in depression

Abstract: A hypothesis is presented that attempts to describe the mechanism by which noradrenergic neurons in the brain influence dopaminergic neurons to produce behavioral changes seen in depression. The historical background pointing to a norepinephrine (NE)‐dopamine (DA) interaction in depression is described. This interaction is suggested by numerous observations indicating that whereas NE is important in therapy and pathogenesis of depression, basic research implicates DA in depression‐related behavioral responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 131 publications
1
25
0
Order By: Relevance
“…In agreement, a number of studies have shown that there is a reduced level of DA and its metabolites in the CSF of depressed patients (Brown and Gershon, 1993) and also a reduced release and metabolism of DA in the basal ganglia of animals subjected to stressors that induce behavioral depression (Cabib and Puglisi-Allegra, 1996). This reduction, however, does not appear to be caused by a direct impairment of the dopaminergic neurons or postsynaptic receptors themselves (Weiss et al, 1996;Cabib et al, 1998;Ossowska et al, 2001;Herman et al, 1984;ZebrowskaLupina et al, 1988), but may occur instead in an afferent system that modulates dopaminergic function. One such afferent system that is particularly sensitive to stress and has been implicated in depressive illness is the a 1 -adrenergic (Lipinski et al, 1987;.…”
Section: Role Of a 1 -Adrenoceptors In Behavioral Activitymentioning
confidence: 55%
See 1 more Smart Citation
“…In agreement, a number of studies have shown that there is a reduced level of DA and its metabolites in the CSF of depressed patients (Brown and Gershon, 1993) and also a reduced release and metabolism of DA in the basal ganglia of animals subjected to stressors that induce behavioral depression (Cabib and Puglisi-Allegra, 1996). This reduction, however, does not appear to be caused by a direct impairment of the dopaminergic neurons or postsynaptic receptors themselves (Weiss et al, 1996;Cabib et al, 1998;Ossowska et al, 2001;Herman et al, 1984;ZebrowskaLupina et al, 1988), but may occur instead in an afferent system that modulates dopaminergic function. One such afferent system that is particularly sensitive to stress and has been implicated in depressive illness is the a 1 -adrenergic (Lipinski et al, 1987;.…”
Section: Role Of a 1 -Adrenoceptors In Behavioral Activitymentioning
confidence: 55%
“…As noted above, since some degree of arousal is necessary for behavioral activation to occur, some degree of noradrenergic stimulation of these other a 1 -receptors would be necessary to permit behavioral activation by the putative EPI-a 1 -system. High noradrenergic activity in these areas, however, which occurs during severe anxiety, may suppress behavioral activation (Weiss et al, 1996;Weiss et al, 1998).…”
Section: Epi As An Endogenous Neurotransmitter At a 1 -Receptorsmentioning
confidence: 99%
“…A second hypothesis that can explain many of these same findings was advanced by Weiss et al (1996) regarding the role of NE and its cotransmitter, galanin, in LC neurons. These authors proposed that at moderate rates of firing, LC neurons primarily release NE in target areas, one of which is the ventral tegmental area (VTA).…”
Section: Alternative Hypothesismentioning
confidence: 94%
“…Changes in brain dopamine seem much more promising in this regard, being clearly linked to motor activity and reward-related processes. To all of these investigators this commentator acknowledges his debt in formulating a new hypothesis that was recently published in Depression (Weiss et al 1996). In that article, we postulated that hyperactivity of locus coeruleus (LC) neurons can inhibit firing of dopaminergic cells in the ventral tegmentum (VTA) via galanin release from LC terminals in VTA, an hypothesis that has the potential for linking a major noradrenergic system in the brain that is affected in stress and depression with a dopaminergic system that appears able to mediate some of the important behavioral changes seen in depression.…”
mentioning
confidence: 94%